THE CSR-COMMUNITY GAP: STRATEGIES FOR BETTER ALIGNMENT – A REFLECTIVE ANALYSIS - Tasphi, Ankana; Sharma, Akshita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Companies Act, 2013 mandates that corporations undertake socially responsible initiatives, with Schedule VII outlining diverse areas aimed at improving the welfare of marginalized communities. While the provisions are broad enough to allow flexibility based on corporate interests, implementation often falls short of addressing the actual needs of communities. This paper examines the misalignment between CSR interventions and community priorities, analyzing three key contributing factors. First, the paper highlights how CSR projects are typically designed and approved at the corporate level, with minimal involvement from the intended beneficiaries. This top-down approach creates a disconnect between planned initiatives and the real needs of communities. Second, internal corporate policies often prioritize customer interests over community welfare, creating conflicts that discourage companies from challenging existing frameworks. Finally, the paper explores potential strategies to bridge this gap, ensuring CSR efforts are more responsive to community needs.